Penguatan Kompetensi Mengajar Calon Guru Pendidikan Agama Islam - Rudi Muhamad Barnansyah (Universitas Negeri Jakarta, 2023)
The study aimed to find out the implementation of the basic skills competencies for teaching PAI teacher candidates. Strengthening the teaching skills of prospective PAI teachers in the digital era does not only focus on mastering the material but demands skills in applying digital-based learning media, in addition to other teaching skills. This research focuses on strengthening the teaching competence of PAI (Micro Teaching) teacher candidates. The research method used descriptive qualitative. The subjects of this study were students in the PAI study program who were taking the Teaching Competency Development (Micro Teaching) course. The results of research on strengthening the teaching competence of Islamic education teacher candidates can be carried out through stimulus and response activities. Stimulus reinforcement can be done with habituation, material enrichment and assignments. The strengthening of the response can be done through the results of student learning in the Teaching Competency Development (Micro Teaching) course. As for the overall results of student mastery of each component of teaching skills, the percentage is above 67%, which is good.